(untitled) - Jakeman, Vanessa (Thành phố Hồ Chí Minh, 2002)
Nội dung giới thiệu những kỹ năng và chỉ dẫn thi chương trình IELTS như nghe, nói, đọc, viết...
Keywords: English language,English language,Test of english as a foreign language; Examinations,Study guides,Textbooks for foreign speakers,Study guides